Technology Use, Preferences, and Capacity in Injured Patients at Risk for Posttraumatic Stress Disorder. Issue 3 (3rd July 2017) - Kelly, Cory M.; Van Eaton, Erik G.; Russo, Joan E.; Kelly, Victoria C.; Jurkovich, Gregory J.; Darnell, Doyanne A.; Whiteside, Lauren K.; Wang, Jin; Parker, Lea E.; Payne, Thomas H.; Mooney, Sean D.; Bush, Nigel; et al.
Abstract : Objective : This investigation comprehensively assessed the technology use, preferences, and capacity of diverse injured trauma survivors with posttraumatic stress disorder (PTSD) symptoms. Method : A total of 121 patients participating in a randomized clinical trial (RCT) of stepped collaborative care targeting PTSD symptoms were administered baseline one-, three-, and six-month interviews that assessed technology use. Longitudinal data about the instability of patient cell phone ownership and phone numbers were collected from follow-up interviews. PTSD symptoms were also assessed over the course of the six months after injury. Regression analyses explored the associations between cell phone instability and PTSD symptoms. Results : At baseline, 71.9% ( n = 87) of patients reported current cell phone ownership, and over half (58.2%, n = 46) of these patients possessed basic cell phones. Only 19.0% ( n = 23) of patients had no change in cell phone number or physical phone over the course of the six months postinjury. In regression models that adjusted for relevant clinical and demographic characteristics, cell phone instability was associated with higher six-month postinjury PTSD symptom levels ( p < 0.001). Conclusions : Diverse injured patients at risk for the development of PTSD have unique technology use patterns, including high rates of cell phone instability. These observations should be strongly considered when developing technology-supported interventions for injured patients with PTSD.